EFEKTIVITAS EKSTRAK DAUN SIRSAK SEBAGAI INHIBITOR PADA BAJA KARBON API 5L DALAM LARUTAN NaCl 3% - Apriyanto Supriyo Giri; Ediman Ginting; S Suprihatin (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2017)
The effectiveness of soursop leaves extract as inhibitor on carbon steel API 5L in NaCl 3% had been researched. Carbon steel API 5L submersion used NaCl 3% had been done for 144 hours with various concentrations of soursop leaves extract inhibitor adding 0%, 5%, 10%, 15%, 20%, 25%, 30%, and 35%. The research of corrosion rate was done by weight loss and electrochemistry methods. The result showed that the higher percentage of soursop leaves extract inhibitor used, the corrosion rate will decrease and capability of inhibit corrosion will increase. The greatest effectiveness of corrosion occurred at concentration of 35% in NaCl 3% and the effectiveness is 86,16%. The X-Ray Diffraction (XRD) characterization result showed that the phase formed is pure Fe. Scanning Electron Microscopy (SEM) characterization showed uneven clusters and smaller size, fewer holes and cracks too with soursop leaves extract inhibitor 35% than soursop leaves extract inhibitor 0%. Energy Dispersive Spectroscopy (EDS) characterization on sample with inhibitor 0% obtained Cl element.